PRES, a diagnostic dilemma in pregnancy: three case series with unusual presentation - Mansingh, Sudhir; Rai, Gunjan; Bhardwaj, Bikram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Authors report a series of three cases of unusual presentation of posterior reversible encephalopathy syndrome in pregnancy. First patient, 29 years old G2P1L1, who was a booked case at our hospital, presented with complain of no fetal movement perception for 3 days at 27 weeks of period of gestation. No history of hypertension and even no record of hypertension after admission. On USG detected to have severe early onset IUGR and AEDF in Umbilical artery doppler. Went in to spontaneous labor and delivered vaginally a preterm neonate of birth weight of 740 gms at 27 weeks 06 days of period of gestation. Postpartum period was uneventful till day four and on day five of postpartum she developed severe headache and seizure. MRI done which was suggestive of PRES. Second patient 27 years old primi gravida with 37 weeks 01 day, booked at our hospital with regular ANC visit brought with history of headache, vomiting with semi-conscious state with diminution of vision till finger count only. She developed seizure thrice while examination. Antenatal period was uneventful with no history of hypertension. Underwent emergency LSCS on same day and delivered a 2.8 kg healthy female neonate. Patient treated as a case of eclampsia and later MRI findings were suggestive of PRES. Third patient 19 years old primigravida booked ANC case at another hospital. She underwent emergency LSCS at 39 weeks POG for fetal distress at same hospital. Antenataly no history of hypertension or any other co-morbidity. On fourth post-op day, she developed headache and vomiting followed by one episode of seizure and after initial management she transferred to our hospital for further management. When we received patient, she was on Magsulph infusion considering postnatal eclampsia. We managed with Inj Lorazepam 2 mg intravenous and later with Inj Levetiracitam. Final diagnosis has been made as PRES after MRI and MRV brain. We found very atypical presentation of all three cases with difficulty in diagnosis and challenging management, so we are reporting these cases.